foF2 Seasonal Asymmetry Diurnal Variation Study during Very Quiet Geomagnetic Activity at Dakar Station - Sibri Alphonse Sandwidi; Doua Allain Gnabahou; Frédéric Ouattara (International Journal of Geophysics)
This paper aims to study the foF2 seasonal asymmetry diurnal variation at Dakar station from 1976 to 1995. We show that equinoctial asymmetry is less pronounced and somewhere is absent throughout 21 and 22 solar cycles. The absence of equinoctial asymmetry may be due to Russell-McPherron mechanism and the vertical drift E×B. The solstice anomaly or annual anomaly is always observed throughout both 21 and 22 solar cycles as measured at Dakar ionosonde. The maximum negative value of σfoF2, fairly equal to -65%, is observed during the decreasing phase at solstice time; this value appeared usually at 0200 LT except during the maximum phase during which it is observed at 2300 LT. The maximum positive value, fairly equal to +94%, is observed at 0600 LT during solar minimum at solstice time. This annual asymmetry may be due to neutral composition asymmetric variation and solar radiation annual asymmetry with the solstice time. The semiannual asymmetry is also observed during all solar cycle phases. The maximum positive value (+73%) is observed at 2300 LT during solar maximum, and its maximum negative (-12%) is observed during the increasing phase. We established, as the case of annual asymmetry, that this asymmetry could not be explained by the asymmetry in vertical velocity E×B phenomenon but by the axial mechanism, the “thermospheric spoon” mechanism, and the seasonally varying eddy mixing phenomenon.